The Effectiveness of Non Pharmachological Therapy on Fatigue Level in Patients With Congestive Heart Failure (CHF) - Gede, Khrisna Eka Yudha; Kamaryati, Ni Putu; Adiana, I Nengah; Sutini, Kadek (Babali Nursing Research, 2023)
The consumption of large number of drugs in a long period of time makes CHF patients experience anxiety so that it faster to cause fatigue due to physical and psychological problems experienced. In addition, special measures to overcome fatigue conditions in patients with CHF are still rarely done. Without significant treatment efforts, it will cause serious problems for patients for a long time, therefore it is very necessary to study the effectiveness of non-pharmacological therapy for patients with CHF. This study aims to collect and analyze articles related to the effectiveness of non-pharmacological therapy in patients with congestive heart failure. This study is a type of literature review conducted by searching for articles related to effective non-pharmacological therapies to reduce fatigue in heart failure patients. The databases used were Pubmed, Google Scholar, and Pro Quest. Inclusion criteria used for data collection are complete articles, journal publications from 2018 to 2023, in English and Indonesian. The tools and guidelines used utilized the PRISMA method. Non-pharmacological therapies used such as back massage, hypnosis and virtual reality provide effects that will cause relaxation and can stimulate the release of endorphins to reduce the activity of the sympathetic and parasympathetic systems. Six studies (85%) of the total seven studies analyzed showed significant results that non-pharmacological therapies resulted in a significant reduction in fatigue. Each non-pharmacological therapy provided has its own stimulation and effect on the patient which will be effective according to the condition and physical problems experienced by the patient. This systematic review shows that non-pharmacological therapy is an effective therapy in reducing the level of fatigue in patients with congestive heart failure according to the psychological state and physical problems experienced by patients. The results of this study are expected to be the basis for complementary therapy and can be implemented as an independent and innovative intervention in nursing care.